Bidirectional Relationship Between Cancer and Heart Failure: Insights on Circulating Biomarkers - Chianca, Michela; Panichella, Giorgia; Fabiani, Iacopo; Giannoni, Alberto; L'Abbate, Serena; Aimo, Alberto; Del Franco, Annamaria; Vergaro, Giuseppe; Grigoratos, Chrysanthos; Castiglione, Vincenzo; Cipolla, Carlo Maria; Fedele, Antonella; et al. (Frontiers in Cardiovascular Medicine, 2022)
Cancer and heart failure are the two leading causes of death in developed countries. These two apparently distinct clinical entities share similar risk factors, symptoms, and pathophysiological mechanisms (inflammation, metabolic disturbances, neuro-hormonal and immune system activation, and endothelial dysfunction). Beyond the well-known cardiotoxic effects of oncological therapies, cancer and heart failure are thought to be tied by a bidirectional relationship, where one disease favors the other and vice versa. In this context, biomarkers represent a simple, reproducible, sensitive and cost-effective method to explore such relationship. In this review, we recapitulate the evidence on cardiovascular and oncological biomarkers in the field of cardioncology, focusing on their role in treatment-naïve cancer patients. Cardioncological biomarkers are useful tools in risk stratification, early detection of cardiotoxicity, follow-up, and prognostic assessment. Intriguingly, these biomarkers might contribute to better understand the common pathophysiology of cancer and heart failure, thus allowing the implementation of preventive and treatment strategies in cardioncological patients